Serum Proteomic Analysis Revealed Biomarkers for Eosinophilic Chronic Rhinosinusitis with Nasal Polyps Pathophysiology - Chen Y; Gao R; Liu H; Ye M; Chu L; Wang T (Dove Medical Press, 2024)
Yu Chen,1 Ru Gao,1 Honghui Liu,1 Maoyu Ye,1 Ling Chu,2 Tiansheng Wang1 1Department of Otolaryngology-Head and Neck Surgery, the Third Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 2Department of Pathology, the Third Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of ChinaCorrespondence: Tiansheng Wang, Department of Otolaryngology-Head and Neck Surgery, the Third Xiangya Hospital, Central South University, 138 Tongzipo Road, Yuelu District, Changsha, People's Republic of China, Email 600923@csu.edu.cnBackground: Individuals with eosinophilic chronic rhinosinusitis with nasal polyps(eCRSwNP) exhibited worse outcomes and higher postoperative recurrence rates. This study aimed to identify biomarkers that can aid in the early differentiation of eCRSwNP and enhance our comprehension of its pathophysiology.Methods: We recruited two independent cohorts. In the discovery cohort, CRSwNP was categorized into eCRSwNP and non-eosinophilic CRSwNP(neCRSwNP), and serum proteomics was performed to identify differentially expressed proteins between the two groups. These candidate proteins were chosen and confirmed in the validation cohort using an enzyme-linked immunosorbent assay (ELISA), Western blot (WB), quantitative real time-polymerase chain reaction (qRT-PCR), immunofluorescence (IF), and their predictive values and associations with tissue eosinophilic pathophysiology were evaluated.Results: We identified a total of 39 differential proteins between the two groups, including 20 proteins upregulated and 19 downregulated in the eCRSwNP group. Further validation was conducted on the top 5 proteins that were up or down-regulated. Results from the ELISA showed that levels of serum MRC1, CDH13, and MMP2 were significantly higher, TRIM28 was lower in the eCRSwNP group compared to the neCRSwNP group (all P< 0.05), and serum MRC1 (AUC=0.742, P< 0.001) and MMP2 (AUC=0.766, P< 0.001) levels exhibited promising predicting values for eCRSwNP. Moreover, qRT-PCR and WB analysis found that MMP2 and MRC1 expressions were enhanced in the eCRSwNP group compared to the neCRSwNP group (all P< 0.01), and their levels were positively correlated with the number and percentages of tissue eosinophils (all P< 0.01). The IF suggested that MMP2 and MRC1 were overexpressed in the nasal polyps tissues of eCRSwNP patients, and MMP2 was mainly located on eosinophils.Conclusion: Circulating proteins identified by proteomics could serve as potential preoperative biomarkers for distinguishing eCRSwNP. Among them, MMP2 was enhanced in eCRSwNP and correlated with tissue eosinophilia, which provided valuable insights into the pathophysiology of eCRSwNP.Keywords: chronic rhinosinusitis with nasal polyps, endotype, eosinophilic, proteomics